Electrochemical method of pyrophosphate determination by quinone reduction. (20th March 2019) - Xu, Wenwen; Shao, Cuimin; Pang, Junjie; Jiang, Yuchun; Han, Yinghui; Wang, Jianguo
Abstract: An electrochemical method to determine pyrophosphate (PPi) was developed using a glassy carbon electrode. PPi displays a new cathodic peak under a positive potential during benzoquinone (BQ) reduction. This new peak is caused by a sharp change in pH near the electrode surface. At pH 4.500, one mole of PPi is hydrolyzed to form two moles of H2 PO4 −, leading to a new intense cathodic peak. The peak current difference of the two new peaks, which is caused by PPi hydrolysis, depends on the PPi concentration but not the BQ concentration. The peak current difference is linearly related to PPi concentrations in the range of 1.0 × 10 −5 –7.0 × 10 −4  mol L −1  (R 2  = 0.998). Moreover, H2 PO4 −, NaF, NaCl, sugar, and acesulfame do not affect the peak current difference. The proposed method was applied to measure the PPi content of toothpaste samples.